2014
DOI: 10.1111/cas.12529
|View full text |Cite
|
Sign up to set email alerts
|

Expression of L‐type amino acid transporter 1 (LAT1) as a prognostic and therapeutic indicator in multiple myeloma

Abstract: L-type amino-acid transporter 1 (LAT1) plays a key role in cell growth and survival. To determine the prognostic significance of LAT1 in multiple myeloma (MM), we investigated the expression of LAT1 and its functional subunit, 4Fc heavy chain (CD98), on myeloma cells by immunohistochemistry in 100 newly diagnosed MM patients. High expression (moderate or strong staining intensity) of LAT1 and CD98 was detected in 56% and 45% of patients, respectively. The LAT1 expression score was positively correlated with Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 45 publications
(47 reference statements)
3
91
1
1
Order By: Relevance
“…Finally, we show that LAT1 overexpression is consistently associated with poor relapse free survival in four independent clinical datasets from ER+ patients that received an endocrine therapy. This observation is consistent with other reports that LAT1 may be an indicator of poor prognosis 25,61 . Taken together with the mechanistic outcomes reported here, further study of LAT1 and its role in endocrine therapy resistance may lead to novel therapeutic alternatives to improve overall survival for patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Finally, we show that LAT1 overexpression is consistently associated with poor relapse free survival in four independent clinical datasets from ER+ patients that received an endocrine therapy. This observation is consistent with other reports that LAT1 may be an indicator of poor prognosis 25,61 . Taken together with the mechanistic outcomes reported here, further study of LAT1 and its role in endocrine therapy resistance may lead to novel therapeutic alternatives to improve overall survival for patients.…”
Section: Discussionsupporting
confidence: 94%
“…LAT1 is responsible for the uptake of leucine and tyrosine for protein synthesis or as intermediates to enter the TCA cycle 19,53,54 . Increased LAT1 expression has been reported in several cancers including prostate cancer 22 , pleural mesothelioma 24 , multiple myeloma 25 and non-small cell lung cancer 26 . Since homozygous knockout of LAT1 in embryonic lethal 28 , LAT1 is critical for growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…For example, human PON3 is markedly overexpressed in a variety of human neoplasias and has antiapoptotic function (Schweikert et al, 2012). The role of another HOC gene, SLC7A7, is poorly understood but its relative SLC7A5 (LAT1) is associated with high proliferation and poor prognosis in newly diagnosed patients with multiple myeloma – a B cell malignancy (Isoda et al, 2014). Altogether, these data strongly suggest that HOC signature contains oncogenic drivers of CLL that contribute to the transformation of B-1a cells.…”
Section: Discussionmentioning
confidence: 99%
“…L-type amino-acid transporter 1 (LAT-1) mediates sodium-independent cellular transport of amino acids for protein synthesis and other metabolic pathways, and high levels of LAT-1 correlate with proliferating cancers. Isoda et al have demonstrated expression of LAT-1 by immunohistochemistry in 100 MM patients and found LAT-1 in 56% of patients (28). The 18 F-labeled amino acid 3,4-dihydroxy-6- 18 F-fluoro-L-phenylananine is a tracer for imaging LAT-1 and warrants evaluation as a PET marker of prognosis and therapeutic planning and response in MM.…”
Section: Pet Imaging In MMmentioning
confidence: 99%